Perilaku Caring menurunkan Kecemasan Pasien Preoperasi - Sulastri Sulastri; Ade Ira Cahyanti; El Rahmayati (Jurnal Kesehatan, 2019)
Invasive actions are closely related to psychological problems, special feelings of anxiety. Uncertain health conditions during and after procedures that can occur during surgery are decided for the patient's recovery. Need special methods from nurses to help patients cope with anxiety, such as caring nurses caring. The purpose of this study is to know the effect of the caring behavior of nurses on preoperative patient's anxiety levels. This research uses a quasi-experimental approach l design with a pretest-posttest one group design. This study was conducted in June 2018 in the Surgical Inpatient Room RSUD Dr.H Abdul Moeloek Lampung Province. The technique of sampling using nonprobability by purposive sampling, got a sample counted 38 respondents. Bivariate analysis using paired sample t-test. The result showed that the average score of the respondent anxiety index before caring behavior of nurse was 40,50 and the score after caring behavior was 34,63. The difference in the mean score of anxiety index score before and after caring behavior was 5.87 with the p-value of 0.000. Based on the conclusion of the research, the writer suggests that the interaction of nurses to the patient is improved and the Standard Operating Procedure of the frequency and duration of the nurse contact to the patient especially the preoperative patient can develop the use of the Caring Dimensions Inventory which covers biological, psychological, social and spiritual aspects.